203 Effect of Feed Intake and Calcium Salts of Palm Oil Inclusion on Growth Performance and Carcass Characteristics of Feedlot Finishing Steers. (12th April 2022) - Pittaluga, Alejandro; Ortiz, Mairim; Relling, Alejandro E
Abstract: Fifty-nine Angus×SimAngus-crossbred steers [body weight (BW) 279 ± 16 kg] were used to evaluate the effect of different dry matter intake (DMI; FS) with or without the inclusion of palm oil calcium salts (4% dry matter basis; CSPO) on growth and carcass characteristics of feedlot steers. Steers were blocked by BW and randomly assigned to individual pens. Treatments (2×2 factorial) consisted of ad-libitum ground corn (GC)-based diet without (ANF) or with (AWF) the inclusion of CSPO, or 85% of the DMI of the ANF treatment without (RNF) or with the inclusion of CSPO (RWF). After weaning, steers were fed a corn silage-based diet for 30-d and subsequently placed in a GC-based diet. Both diet types were offered ad-libitum or at 85% of the ANF intake and with or without CSPO. After 59-d in the finishing diet, all steers had ad-libitum access to feed. All data were analyzed with a mixed model considering the fixed effect of treatments, time and their interaction, and random effect of block. There were FS×CSPO interactions (Table 1; P ≤ 0.01) for BW, DMI, average daily gain (ADG) during the first 106-d. After all steers were switch to ad-libitum, restrictedly fed steers had greater ( P ≤ 0.01) ADG and ADG:DMI ratio (G:F) compared with ad-libitum fed steers. No treatment differences ( P ≤ 0.21) were observed for final BW (FBW), and overall DMI, and G:F. No treatment or their interactions ( P ≥ 0.34) were detected for any carcass characteristic (Table 2) except for longissimus muscle area (LMA, P = 0.07), where CSPO inclusion tended to increase the LMA of steers fed ad-libitum but did not differ from restricted steers. Therefore, differences in growth as a consequence of intake restrictions during the growing and early finishing stage could be mitigated once cattle are allowed ad-libitum access to feed.